2020
DOI: 10.3897/zookeys.969.52334
|View full text |Cite
|
Sign up to set email alerts
|

Distributional records of Ross Sea (Antarctica) planktic Copepoda from bibliographic data and samples curated at the Italian National Antarctic Museum (MNA): checklist of species collected in the Ross Sea sector from 1987 to 1995

Abstract: Distributional data on planktic copepods (Crustacea, Copepoda) collected in the framework of the IIIrd, Vth, and Xth Expeditions of the Italian National Antarctic Program (PNRA) to the Ross Sea sector from 1987 to 1995 are here provided. Sampling was performed with BIONESS and WP2 nets at 94 sampling stations at depths of 0–1,000 m, with a special focus on the Terra Nova Bay area. Altogether, this dataset comprises 6,027 distributional records, out of which 5,306 were obtained by digitizing original data repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…The current paper represents a further contribution of the Italian National Antarctic Museum (MNA)-Genoa section, as custodian of biodiversity data for the Ross Sea area. Many contributions to the Antarctic Biodiversity Portal have been published by MNA over the years, with the aim of increasing the knowledge of the area [89][90][91][92][93][94][95][96] (http://www.biodiversity.aq, accessed on 8 February 2022). It is desirable that in the next years, all available museum collections will be subject to molecular identifications in order to precisely determine species ranges and occurrences, key data for all monitoring activities.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The current paper represents a further contribution of the Italian National Antarctic Museum (MNA)-Genoa section, as custodian of biodiversity data for the Ross Sea area. Many contributions to the Antarctic Biodiversity Portal have been published by MNA over the years, with the aim of increasing the knowledge of the area [89][90][91][92][93][94][95][96] (http://www.biodiversity.aq, accessed on 8 February 2022). It is desirable that in the next years, all available museum collections will be subject to molecular identifications in order to precisely determine species ranges and occurrences, key data for all monitoring activities.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Systemic biological research in TNB resulted in the discovery of a variety of taxa new to science, including ampharetids, amphipods, Porifera and coralline algae (e.g., [37,38,[45][46][47][48][49]). Checklists of species from TNB are systematically published and updated by the Italian national Antarctic Museum (MNA, Section of Genoa) [49][50][51][52][53]. The evidence of high diversity at both species and community levels fuelled the establishment of the Antarctic Specially Protected Area (ASPA) No.…”
Section: Study Areamentioning
confidence: 99%
“…Copepod communities in the Ross Sea area have been extensively studied since 1985 and were part of the objectives of the first Italian Ocenographic Expeditions of the PNRA ( Amato 1990 ). The scientific team of those expeditions studied the biodiversity and ecological roles of planktonic copepods ( Carli et al 1989 , Carli et al 1990 , Zunini Sertorio et al 1990 , Guglielmo et al 1990 , Zunini Sertorio et al 1992 , Bonello et al 2020 , Carli et al 2000 , Zunini Sertorio et al 2000 , Carli et al 2002 , Pane et al 2004 , Grillo et al 2022 ) and their association with pack-ice ( Guglielmo et al 2007 , Granata et al 2009 , Guglielmo et al 2015 , Granata et al 2022 ); however, to date, information regarding the diversity of benthic copepods is still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In Bonello et al (2020) , a total of 8,224 specimens of Antarctic copepods are reported, after the analysis of materials from the III rd , V th and X th Italian Antarctic expeditions, which led to the production of the first checklist for this taxon in the area. This checklist, in addition to the physical samples currently deposited in the biological collection of the Italian National Antarctic Museum (MNA), contains the digitised data, mostly belonging to grey literature, recovered from the PNRA expedition reports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation